Tamarix dioica (Ghaz) Protective Potential in the Carbon Tetrachloride-Induced Hepatotoxicity Animal Model - Sumra Komal; Aqna Malik; Naheed Akhtar; Syed Asif Jahanzeb Kazmi; Fayyaz Anjum; Ayesha Rida (Proceedings, 2021)
Introduction: Hepatic diseases remain the leading cause of death worldwide. Despite overall advancements in health care, mortality due to hepatic diseases is constantly growing. More than 2 million people globally are estimated to die each year from liver diseases, and current treatment offers little for its management. Thus, it is essential to find more effective and less toxic pharmaceutical alternatives for the treatment of liver diseases. Aims & Objectives: Tamarix dioica, a shrub broadly used in herbal medicine for the treatment and prevention of various diseases. The current study was designed to analyze the hepatoprotective effect of T. dioica in BALB?cmice against CCl4-induced acute liver damage. Place and duration of study: The study was conducted in NIH, Islamabad, Pakistan, for six months in 2016-2017. Material & Methods: For in vivo evaluation, the animals (n= 42) were randomly divided into seven groups (n=6), three control (i.e. Group, I or normal control, group II or induction control received 0.9% normal saline orally, and Group III or positive control received silymarin 100 mg/kg per oral), and four treatment groups (i.e. IV, V,VI and VII were treated with oral T.dioica 200 mg/kg/day, 300mg/kg/day methanol extract, 200mg/kg/day and 300mg/kg/day of aqueous extracts respectively for six days, followed by intraperitoneal administration of CCl4 on the seventh day. The blood samples were collected for analysis of LFTs, and hepatic tissue was taken for histological analysis. Data was analyzed using SPSS version 16, one-way ANOVA with Duncan’s Multiple Range Test (DMRT). Results: CCl4 induction in Group 2 resulted in severe hepatic derangement manifested as highly elevated mean LFTs (ALT 7245.56, AST 3292.11, ALP 340.09 U/L, bilirubin 4.64 mg/dl) as compared to healthy controls (ALT 38.97, AST 50.20, ALP 57.17 U/L, bilirubin 1.25 mg/dl: (Group 1) levels p<0.001. Pretreatment with different extracts of T.dioica for 6 days before CCl4 administration produced varying degrees of hepatoprotection. 300mg/kg aqueous extract T.dioica (Group7) prevented damage with maximal hepatoprotection, reduced LFTs (ALT: 339.95 , AST: 242.90 , ALP: 116.86 U/L, bilirubin: 1.38 mg/dl) and normalized liver histology as compared to Group 2 and standard drug silymarin 100mg/kg, (ALT: 6483.23, AST: 2567.69, ALP: 272.19 U/L, bilirubin: 2.84 mg/dl: Group 3) p<0.001. Lesser hepatoprotection was provided by T.dioica aqueous extract 200mg/kg (ALT: 439.93, AST: 367.87, ALP: 180.62 U/L bilirubin: 1.53 mg/dl: Group VI) and least by 300mg/kg & 200mg/kg methanolic extracts Groups V & IV (ALT: 6338.06, 6443.91, AST: 2800.81, 3012.34, ALP: 242, 248 U/L & bilirubin: 2.82 & 3.62 mg/dl) respectively. Further, no drug-induced toxicity symptoms were observed 24 hours after administration of the high dose oral T. dioica 2000 mg/kg/body weight aqueous and methanolic extracts were administered. Conclusion: Pretreatment with T. dioica extracts especially 300mg/kg aqueous extract reduced acute CCl4-mediated liver damage, ameliorated histopathological as well as biochemical parameters and was free of toxicity in 2000mg/kg /body weight dose in the mice experimental model. T. dioica has potential in hepatoprotective drug research.